Crystal structure of Ca2Zn2(V4O14) and Pb2Cd2(V3O10)(VO4) double vanadates. Issue 3 (14th June 2018) - Zhuravlev, V. D.; Tyutyunnik, A. P.; Chufarov, A. Y.; Lobachevskaya, N. I.; Velikodnyi, A. A.
Abstract : Polycrystalline samples of Ca2 Zn2 (V4 O14 ) (I) and Pb2 Cd2 (V3 O10 )(VO4 ) (II) were synthesized using the nitrate–citrate method (I) and conventional solid state reaction (II). The structural refinement based on X-ray powder diffraction data showed that the crystal structure of (I) is characterized by monoclinic symmetry with unit-cell parameters a = 6.8044(1) Å, b = 14.4876(3) Å, c = 11.2367(2) Å, β = 99.647(1)° [space group P 21 / c (No. 14), Z = 4], and the crystal structure of (II) is triclinic with unit-cell parameters a = 7.03813(6) Å, b = 12.9085(1) Å, c = 6.99961(5) Å, α = 90.7265(5)°, β = 96.3789(5)°, γ = 94.9530(6)°, V = 629.470(8) Å 3 [space group P $\bar 1$ (No. 2), Z = 2].